Early Platelet Activation by Low Density Lipoprotein via p38MAP Kinase - Hackeng, Christian M.; Relou, Ingrid A. M.; Pladet, Marc W.; Gorter, Gertie; van Rijn, Herman J. M.; Akkerman, Jan-Willem N. (Thrombosis and Haemostasis, 1999)
Low Density Lipoprotein (LDL) is known to sensitize platelets for physiological agonists. To clarify the basis of this sensitization, we investigated the involvement of p38MAP Kinase (p38MAPK). As dual phosphorylation on Thr180 and Tyr182 of p38MAPK is the trigger for activation of the kinase, p38MAPK-activity was measured with an antibody that recognizes the dual-phosphorylated sequence. LDL induced a rapid and dose dependent activation of p38MAPK. The activation was not inhibited by a wide variety of inhibitors of platelet signalling, including TxA2-formation, Phospholipase C-activation, Ca2+-mobilization and ERK 1/2-activation. Only a slight reduction in p38MAPK-activation was observed when protein kinase C was inhibited. Activation of p38MAPK was strongly inhibited by a rise in cAMP. Thus, p38MAPK-activation was upstream of most signalling pathways and close to the LDL-receptor. A number of platelet receptors was screened with the use of antibodies. Integrins αIIbβ3 and α2β1, as well as the FcγRII-receptor, CD36 (platelet glycoprotein IV), CD68 (gp110) and Low Density Lipoprotein-receptor related protein (LRP) were not implicated in LDL-induced p38MAPK-activation. Inhibition of LDL binding by modification of apo B100 lysines reduced p38MAPK-activation by 80 %. Activation of p38MAPK resulted in an increase in release of arachidonic acid, the precursor for thromboxane A2 synthesis. In conclusion, activation of p38MAPK might be the first step in platelet sensitization by LDL, leading to formation of arachidonate metabolites and increased aggregation and secretion responses to physiological agonists.
Keywords: LDL; lipoproteins; mapkinase; platelet